Analysis of the Misconceptions Taking Accounting Education Students About Accounting Education: Example of TRB 1 Region - Gul, Meltem; Demir, Ozcan; Narlikaya, Zulkuf (Mehmet Akif Ersoy Univ, 2024)
Misconceptions are encountered in the field of accounting education as in every field. Since misconceptions in the field of education will affect the student's future life, these misconceptions should be identified and eliminated in advance. This study aims to determine the misconceptions of accounting education students about accounting education. For this purpose, the Misconceptions Analysis in Accounting Education (MAAE) scale was applied to the students who continue their education in the departments of business administration, business administration and accounting/tax practices at the undergraduate and associate degree level of state universities in TRB 1 region. The data collected within the scope of the research were analysed in SPSS 22 programme. According to the results of the research, it was determined that the perceptions of misconceptions about accounting of students studying accounting education are high, and the highest misconceptions are related to the idea that accounting is a recording process and students' general accounting knowledge. It has been observed that the general accounting course is perceived by the students as a course in which general information is given as an introduction to accounting. With this perception, the student associated the course as easier in his/her mind. However, when they are fully acquainted with accounting education, it becomes difficult for students to perceive the course as a result of the mismatch between their expectations and what they see. With the results obtained from the study, it is expected that the difficulties experienced by the students in accounting courses and the misconceptions they have acquired will be identified and will help to eliminate the mistakes that will be experienced in the name of accounting in the future. It is extremely important to eliminate these misconceptions in order to have a positive impact on the department that students choose as a profession, which will affect their future lives. Eliminating these misconceptions will undoubtedly contribute to increasing the quality of accounting education. It is thought that the results of the study will attract the attention of all academicians interested in accounting education, contribute to the way accounting academicians handle the course and contribute to the misconceptions in the literature.
Keywords: Accounting Education; Accounting Students; Misconception